(untitled) (Ustozlar uchun, 2025)
The Progress in International Reading Literacy Study (PIRLS) is an international assessment designed to measure the reading literacy levels of primary school students, particularly those in the fourth grade. The assessment evaluates not only students’ ability to read texts accurately, but also their capacity to understand, analyze, interpret, and evaluate written information. Despite ongoing educational reforms and curriculum updates, PIRLS results indicate that many students still face challenges in higher-level reading comprehension. This article explores the importance of PIRLS in modern education, identifies key difficulties students experience in real classroom settings, analyzes the main causes of weak reading comprehension, and suggests practical teaching strategies to improve reading literacy. The study emphasizes that improving everyday classroom practices can significantly enhance students’ reading skills and overall academic success.